Bacteriemia in septoplasty and septorhinoplasty surgery - Kaygusuz, I; Kizirgil, A; Karlidag, T; Yalçin, S; Keles, E; Yakupogullari, Y; Alpay, C (Int Rhinologic Soc, 2003)
This study was conducted in an attempt to investigate whether bacteriemia developed in patients with septoplasty and septorhinoplasty in the postoperative period during which an anterior nasal pack was in their nose. Fifty-three patients who went through septoplasty or septorhinoplasty operations were followed in this study. Nasal smear cultures were obtained from all the subjects before the operation. After the packs were retrieved, smears were also obtained from the pack material. Venous blood samples were obtained from the patients immediately before the operation, after the operation and immediately following the retrieval of the pack. When preoperative nasal smear cultures and postoperative pack material cultures of the patients that were obtained at 48 hours were compared, it was seen that different microorganisms were present in 66% of the patients. Bacterial growth was not observed in any of the preoperative blood cultures; whereas 8 patients (15.0%) had bacteriemia in the blood samples obtained immediately after the operation and 9 (16.9%) had growth in the blood samples obtained following the retrieval of the pack. With these results we have seen that bacteriemia can develop in patients with septoplasty and septorhinoplasty. It did not cause serious clinical problems. However, in patients with cardiovascular problems, this possibility should be taken into consideration and relevant preoperative precautions should be implemented.
Keywords: septoplasty; septorhinoplasty; bacteriemia; nasal pack